2017
DOI: 10.1002/aic.15754
|View full text |Cite
|
Sign up to set email alerts
|

In‐line monitoring of hydrogen peroxide in two‐phase reactions using raman spectroscopy

Abstract: Hydrogen peroxide is an environment‐friendly oxidizer, which is used in several chemical processes. However, safety necessitates the determination and control of the concentration of hydrogen peroxide during oxidation reactions. We propose a methodology to monitor hydrogen peroxide in disperse two‐phase reaction mixtures based on in‐line Raman spectroscopy. We compare indirect hard modeling (IHM), peak integration (PI), and partial least squares (PLS). Building predictive PLS and PI calibration models is chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Therefore, the results demonstrated that the 633 nm laser line is the optimal excitation wavelength for SERS measurements and quantitative analysis. Among them, the peak at 876 cm −1 during the GPx4-like catalytic cycle of EGCG was assigned to O − O from H 2 O 2 was observed once H 2 O 2 was added compared to other spectra, which was similar to previous studies ( Ebrahimi, Viell, Mitsos, Mhamdi, & Brandhorst, 2017 ; Ghosh, Prasad, & Mugesh, 2019 ; Molinari & Wachs, 2010 ). During the GPx-like catalytic cycle of EGCG was measured by in-situ SERS spectrum (ranging from 400 to 1800 cm −1 ) and SERS bands were observed at 443, 762, 806, 876, 914, 1178, 1370, and 1620 cm −1 ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…Therefore, the results demonstrated that the 633 nm laser line is the optimal excitation wavelength for SERS measurements and quantitative analysis. Among them, the peak at 876 cm −1 during the GPx4-like catalytic cycle of EGCG was assigned to O − O from H 2 O 2 was observed once H 2 O 2 was added compared to other spectra, which was similar to previous studies ( Ebrahimi, Viell, Mitsos, Mhamdi, & Brandhorst, 2017 ; Ghosh, Prasad, & Mugesh, 2019 ; Molinari & Wachs, 2010 ). During the GPx-like catalytic cycle of EGCG was measured by in-situ SERS spectrum (ranging from 400 to 1800 cm −1 ) and SERS bands were observed at 443, 762, 806, 876, 914, 1178, 1370, and 1620 cm −1 ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…4 In addition, owing to its powerful capability of providing rich information on molecular structure and chemical composition without destruction and preparation of the sample, in-line Raman spectroscopy has been adopted to obtain real-time information in a number of industries such as pharmaceutical, [5][6][7] bioengineering, 8,9 and chemical. 10,11 In polymer fields, the Raman spectroscopy technique has been reported for on-line measurement of crystallinity, [12][13][14] for monitoring polymerization reactions, 15,16 for on-line measurement of polyethylene pellet density, 17 etc. However, due to the harsh environment of the polymer blending processing line and the influence of fluctuating fluorescence background, using in-line Raman spectroscopy to analyze the dispersion uniformity of polymer blends, which is a relatively novel and less studied field, remains to be further explored and developed.…”
Section: Introductionmentioning
confidence: 99%
“…Details on the construction of both spectral mixture hard models together with further information on the theoretical concept of spectral complemental hard modeling and spectral indirect hard modeling are provided in the Supporting Information. The advantages of spectral indirect hard modeling over other multivariate chemometric models, such as often-used partial least squares regression, are the physically meaningful deconvolution of highly overlapping peaks in the spectra of multicomponent mixtures, the compensation of nonlinear effects such as peak shifts or peak deformations due to the interaction of chemical species, the robustness against noise, , a reduced demand of calibration samples, , and the improved range of extrapolation, e.g., in composition and temperature dimension , that have been reported in the literature and are mostly explained by the physically motivated structure of the spectral indirect hard modeling.…”
Section: Methodsmentioning
confidence: 99%